Pterigyum. A case presentation. - Eduardo Rojas Alvarez (Medisur)
This is a 43 year-old patient from Guatemala. He is a fisherman who lives in the Izabal Department. He came to the Nevaj ophthalmological centre, in Quiché, Guatemala complaining of diminishment of his visual acuity and tearing in both eyes. The presence of fibro vascular tissue in the bulbar conjunctiva in both eyes invading the cornea was verified in the anterior biomicroscopy. Bipolar pterigyum degree II in the left eye and nasal pterigyum degree III in the left eye was diagnosed. The patient´s job and the place where he lives are the risk factors associated to this disease. Three surgical treatments were performed using the Exeresis technique and conjunctival autoplasty beginning by the right eye and followed by the left eye and then the right eye again. Only eight days were between each surgical treatment. There was a follow up until one month after the last surgical intervention with no complications at all.